2016
DOI: 10.1371/journal.pone.0161038
|View full text |Cite
|
Sign up to set email alerts
|

The Role of High-Resolution Magic Angle Spinning 1H Nuclear Magnetic Resonance Spectroscopy for Predicting the Invasive Component in Patients with Ductal Carcinoma In Situ Diagnosed on Preoperative Biopsy

Abstract: The purpose of this study was to evaluate the role of high-resolution magic angle spinning (HR-MAS) 1H nuclear magnetic resonance (NMR) spectroscopy in patients with ductal carcinoma in situ (DCIS) diagnosed on preoperative biopsy. We investigated whether the metabolic profiling of tissue samples using HR-MAS 1H NMR spectroscopy could be used to distinguish between DCIS lesions with or without an invasive component. Our institutional review board approved this combined retrospective and prospective study. Tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 21 publications
(22 reference statements)
0
28
0
Order By: Relevance
“…In another study, HRMAS NMR was used to distinguish between ductal carcinoma in situ (DCIS) lesions with or without an invasive component. 106 It showed that the GPC/PC ratio as well as multivariate models discriminated between pure DCIS and DCIS accompanying invasive carcinoma. HRMAS NMR was also used to investigate breast tumor cell lines MCF-7 and MDA-MB-231, along with the nontumor breast cell line MCF-10A, to evaluate cancer metabolism in intact cells.…”
Section: Applicationsmentioning
confidence: 98%
“…In another study, HRMAS NMR was used to distinguish between ductal carcinoma in situ (DCIS) lesions with or without an invasive component. 106 It showed that the GPC/PC ratio as well as multivariate models discriminated between pure DCIS and DCIS accompanying invasive carcinoma. HRMAS NMR was also used to investigate breast tumor cell lines MCF-7 and MDA-MB-231, along with the nontumor breast cell line MCF-10A, to evaluate cancer metabolism in intact cells.…”
Section: Applicationsmentioning
confidence: 98%
“…However, the glycerophosphocholine/phosphocholine ratio as well as the concentrations of myo‐inositol and succinate was significantly higher in the pure DCIS than in DCIS without an invasive component. Orthogonal projections to latent structure‐discriminant analysis models based on the metabolic profiles were able to clearly discriminate between pure DCIS and DCIS without an invasive component …”
Section: Clinical Applicationsmentioning
confidence: 99%
“…Orthogonal projections to latent structure-discriminant analysis models based on the metabolic profiles were able to clearly discriminate between pure DCIS and DCIS without an invasive component. 83 MRS also allows the noninvasive identification and monitoring of triple-negative breast cancer (TNBC) metabolic aberrations. Several human and experimental studies have shown that phosphatidylcholine metabolism is altered in TNBCs and phosphocholine levels are increased in TNBCs.…”
Section: Determination Of Tumor Aggressiveness and Biological Behaviormentioning
confidence: 99%
“…Attesting to clinical translatability, 1 H HR-MAS, thanks to its execution rapidity and capacity to preserve samples for further analyses, has already shown promising results in other cancers. For example, it has been successfully adopted to determine sample quality in real-time during surgery [32], or to aid diagnosis in tumor biopsies [12,33,34]. In the field of bone cancer, further studies may extend 1 H HR-MAS analyses to larger patient cohorts to characterize and compare pathologic conditions.…”
Section: Discussionmentioning
confidence: 99%